The Effects of Cigarette Smoke Exposure on Anthropometric Measurements, Lipid Profile, Fasting Blood Glucose, Fasting Insulin, and Blood Pressure in Overweight/Obese Adolescents - Widjaja, Nur Aisiyah; Claudia Felisia Magdalena Kurube; Febrina Mustika Santoso; Noviyanti, Tausyiah Rohmah; Alexander, Yoppi Yeremia; Keya, Rino Tryanto; Hermanto, Edi; Iitdrie; Ardianah, Eva; Amer Siddiq Amer Nordin (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: Cigarette smoke exposure increases the risk of obesity, metabolic syndrome, hypertension, hyperglycemia, and dyslipidemia. The nicotine content in cigarettes can acutely increase energy expenditure, decrease appetite, and several other chronic diseases such as cardiovascular disease, lung disease, cancer, and so on. Objectives: This study aims to determine the effect of cigarette smoke exposure on anthropometric measurements, lipid profiles, fasting blood glucose, fasting insulin, and blood pressure in overweight/obese adolescents. Methods: This was a cross-sectional study involving overweight/obese adolescents conducted from September to October 2019 to evaluate the effects of tobacco exposure on anthropometric measurements, lipid profile, fasting blood glucose (FBG), fasting insulin, and blood pressure. Results: This study showed no significant differences in the age distribution, body weight, body height, height-for-age z-score (HAZ), hip circumference, body mass index (BMI), BMI-for-age z-score, fasting insulin, FBG, lipid profile, and blood pressure between low, moderate, and high cigarette smoke exposure in overweight/obese adolescents, but the high exposure group had a bigger waist circumference than the moderate exposure group (107,45 + 11,25 vs 99,35 + 11,36 cm, p = 0,019) and low exposure (107,45 + 11,25 vs 99,04 + 12,08 cm, p = 0,015). Conclusion: The degree of exposure to heavy cigarette smoke has a greater waist circumference than exposure to light and moderate cigarette smoke. Cigarette smoke exposure is significantly associated with body weight and hip circumference, and heavy cigarette smoke exposure is prevalent in adolescent boys.